The role of traditional obesity parameters in predicting coronary artery disease among patients undergoing cardiac catheterization: A systematic review - Audai A. Hayajneh; Islam M. Alhusban; Mohammad Rababa; Dania Bani-Hamad; Shatha Al-sabbah (International Journal of Africa Nursing Sciences, 2022)
Objectives: The literature has evidenced the presence of a relationship between coronary artery disease (CAD) and obesity. This systematic review aimed to explore the relationships between traditional obesity parameters and CAD, the controversial findings available, and the knowledge gaps in the literature. Methods: This systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines to review studies available on the following databases: Cumulative Index to Nursing and Allied Health Literature (CINAHL), Medline, PubMed, Cochrane, Science Direct, and Google Scholar. This review was carried out by five expert researchers. The search included studies published between January 2005 and March 2022. Results: There are seven traditional obesity parameters in the literature that have been associated with the risk of the development of CAD or its related symptoms. These parameters are body mass index (BMI), waist-height ratio (WHtR), waist-hip ratio (WHR), body adiposity index (BAI), body shape index (BSI), waist circumference (WC), and hip circumference (HC). Two of these traditional obesity parameters (WHtR and BMI) appeared to be the best indicators of the development of CAD. Conclusion: There is significant contradiction in the findings of previous studies on the best traditional obesity parameter associated with the development of CAD.